The Use of Lesson Writer in Developing English Teaching Materials for Vocational School Students - Lystiana Nurhayat Hakim; Setyo Wati (Institut Agama Islam Negeri Palopo, 2019)
The aim of this study are to find out teachers’ perception toward Lesson Writer in developing English teaching Materials and to investigate teachers’ difficulties in using Lesson Writer to develop English teaching material. The sample of the study consisted of three English teachers. In this study the teachers focused on developing English teaching materials for the tenth grade of TKJ or Computer and Networking Program. The data collection used in this research was questionnaire and interview. The results of this study are the teachers have positive perception toward the implementation of Lesson Writer in developing English teaching materials, however in using Lesson Writer the teachers faced difficulties such as readiness of technology, limited teaching resources to be uploaded in Lesson Writer, and error server in log in Lesson Writer.